Mobile Work, Veterinary Subjectivity and Brexit: Veterinary Surgeons' Migration to the UK. Issue 4 (8th May 2019) - Enticott, Gareth
Abstract: This article extends studies of 'global work' by considering the mobility of veterinary surgeons in the global countryside. The article develops the concept of 'disease ecology': an assemblage of heterogenous actors and relations that inscribe and normalise mobility within professional subjectivities. Disruptions to these disease ecologies can contribute to new patterns of mobility. Drawing on biographical narrative interviews with 35 vets who have migrated to the United Kingdom to work, the article shows how veterinary mobility is shaped by and emerges in response to these disease ecologies. Specifically, the article describes how four narratives – 'the first job', 'escape and adventure', 'the lucky break' and 'staying mobilities' – contribute to veterinary migration to the UK, and how the lived experiences of work and inscriptions of mobile veterinary subjectivities within disease ecologies lead vets to stay in the UK. However, the article also considers the role of Brexit in disrupting established disease ecologies and creating new patterns of veterinary mobilities. In identifying how Brexit challenges vets' sense of place, the article concludes by exploring Brexit's potential impact to the future of veterinary services in the UK.